Event-triggered sliding mode control of nonlinear dynamic systems. (February 2020) - Liu, Xinxin; Su, Xiaojie; Shi, Peng; Shen, Chao; Peng, Yan
Abstract: In this work, the problem of sliding mode observer design is investigated for a class of repeated scalar nonlinear systems via dynamic event-triggered approach. By constructing an event-triggered observer and a sliding mode surface, the system dynamics is obtained and an event-triggered controller is designed to ensure that the closed-loop system trajectories are restricted to the pre-specified sliding region. Sufficient conditions are provided to guarantee that the system dynamics is asymptotically stable with a desired H ∞ performance level. Two illustrative examples are provided to demonstrate the effectiveness and potential of the proposed design method.